THE ROLE OF SPORTS AND CREATIVITY IN STRESS REDUCTION IN PRIMARY SCHOOL CHILDREN (World Bulletin of Education and Learning, 2025)
Sports and creativity play a crucial role in reducing stress in children. They not only help them relax and develop physical and emotional skills but also serve as effective means of self-expression and coping with inner struggles. Parents and teachers can create conditions for these activities to become regular and beloved by children, helping them cope more easily with life's challenges.
Keywords: Emotions, stress, parents, children, teachers, internal, activities, experiences, conditions, sports, support, self-expression, creativity, experience, life's challenges.